Integration Analysis of Transcriptome and Proteome Reveal the Mechanisms of Goat Wool Bending - Liu, Yue; Ding, Yangyang; Liu, Zhanfa; Chen, Qian; Li, Xiaobo; Xue, Xianglan; Pu, Yabin; Ma, Yuehui; Zhao, Qianjun (Frontiers in Cell and Developmental Biology, 2022)
Zhongwei goat is a unique Chinese native goat breed for excellent lamb fur. The pattern of flower spikes of the lamb fur was significantly reduced due to the reduction of the bending of the hair strands with growth. In order to explore the molecular mechanism underlying hair bending with growth, we performed the comprehensive analysis of transcriptome and proteome of skins from 45-days, 108-days and 365-days goat based on TMT-based quantitative proteomics and RNA-seq methods. In the three comparison groups, 356, 592 and 282 differentially expressed proteins (DEPs) were screened, respectively. KEGG pathway analysis indicated that DEPs were significantly enriched in a set of signaling pathways related to wool growth and bending, such as ECM-receptor interaction, PI3K-Akt signaling pathway, PPAR signaling pathway, protein digestion and absorption, and metabolic pathways. In addition, 20 DEPs abundance of goat skin at three development stages were examined by PRM method, which validated the reliability of proteomic data. Among them, KRT and collagen alpha family may play an important role in the development of goat hair follicle and wool bending. COL6A1, COL6A2, CRNN, TNC and LOC102178129 were identified as candidate genes based on combined analysis of transcriptome and proteome data and PRM quantification. Our results identify the differential expressed proteins as well as pathways related to the wool bending of Zhongwei goats and provide a theoretical basis for further revealing the molecular mechanism underlying wool bending of goats.